Effects of Ado-Trastuzumab Emtansine and Fam-Trastuzumab Deruxtecan on Metastatic Breast Cancer Harboring HER2 Amplification and the L755S Mutation. (11th March 2021) - Mukohara, Toru; Hosono, Ako; Mimaki, Sachiyo; Nakayama, Akiko; Kusuhara, Shota; Funasaka, Chikako; Nakao, Takehiro; Fukasawa, Yoko; Kondoh, Chihiro; Harano, Kenichi; Naito, Yoichi; Matsubara, Nobuaki; et al.
Abstract : : Somatic mutations in human epidermal growth factor receptor 2 ( HER2 ) are present in approximately 3% of breast cancers. Some HER2 mutations are activating, and they represent a mechanism of resistance to conventional anti-HER2 therapies such as trastuzumab and lapatinib. Consistently, in patients with HER2 -amplified breast cancer, these mutations are predominantly observed in metastatic tumors obtained after exposure to anti-HER2 systemic therapies, possibly after clonal selection. Therefore, it is rare to find coexistent HER2 mutation and amplification in the early clinical course, and thus, the clinical relevance of HER2 mutation to the sensitivity to HER2-targeted drugs, particularly antibody-drug conjugates (ADCs) such as ado-trastuzumab emtansine (T-DM1) and the recently approved fam-trastuzumab deruxtecan (T-DXd), remains unclear. In this article, we describe a patient with de novo metastatic breast cancer who exhibited both HER2 amplification and the L755S mutation in the untreated primary breast tumor obtained at the initial diagnosis, and the lesion responded to T-DM1 and T-DXd after exhibiting clinical resistance to other HER2-targeted drugs. Our current case findings suggested that anti-HER2 ADCs should be prioritized over conventional trastuzumab- or lapatinib-based therapies for patients with HER2 -amplified and comutated tumors. Key Points : Although HER2 mutations were implicated in resistance to anti-HER2 monoclonal antibodies or HER2 tyrosine kinase inhibitors in preclinical studies, their clinical impact on sensitivity to anti-HER2 drugs is unclear owing to the rarity of concomitant HER2 mutation and HER2 amplification. A case of de novo metastatic breast cancer harboring both HER2 amplification and the L755S mutation in an untreated breast primary tumor displayed clinical resistance to standard trastuzumab- or lapatinib-based therapies but good responses to ado-trastuzumab emtansine (T-DM1) and fam-trastuzumab deruxtecan (T-DXd). Anti-HER2 antibody-drug conjugates such as T-DM1 and T-DXd may be prioritized over conventional trastuzumab- or lapatinib-containing therapies for patients with HER2 -amplified and comutated tumors. Abstract : This article reports the case of a patient with de novo metastatic breast cancer who harbored both HER2 amplification and the L755S mutation in the untreated primary breast tumor obtained at the initial diagnosis, detailing her response to treatment with HER2-targeted drugs.